Seafood markets and trade: a global perspective and an overview of EU Mediterranean countries - Paquotte P.; Lem A. (The Mediterranean fisheries sector. A reference publication for the VII meeting of Ministers of agriculture and fisheries of CIHEAM member countries (Zaragoza, Spain, 4 february 2008), 2008)
World production and supply of fish and fisheries products reached an estimated 143 million tons in 2007, up slightly from 2006 (141 million t). Capture fisheries were stable at 91 million tons whereas aquaculture continues to grow, albeit at a declining rate, reaching 52 million tons in 2007. As a percentage of supplies to human consumption (excluding fish meal), the share of aquaculture has now reached 45%. Trade continues to grow, up 8.1% in 2007 to an estimated US$ 93 billion (export value). Developing countries represent around 50% of exports whereas the US, Japan and the EU take almost 3/4 of all imports. China is the largest producer as well as the largest exporter. One of the major obstacles to increased international trade in fish and fisheries products (beyond physical availability of product) are the quality and safety related import requirements in developed countries, including those related to labelling, certification and traceability. The Mediterranean countries are mainly responsible for the enormous deficit in the trade balance of the European Union for fishery and aquaculture products, Italy holding first place with a deficit reaching almost 2.5 billion euros, followed by France and Spain, each with a deficit of 2 billion euros. The five largest Mediterranean countries of the European Union (France, Greece, Italy, Portugal and Spain) account for 38% of the total population of Europe, but make up approximately 53% of the consumption. The Mediterranean countries are therefore top consumers and deficitary producers of fishery and aquaculture products. These high figures refer particularly to shellfish and crustacean consumption since the five Mediterranean countries account for 72% of the total European consumption of these species, in comparison to 47% for finfish. There is however a wide disparity in the levels of consumption per caput, with almost 55 kilos in Portugal and nearly 50 kilos in Spain, followed by 35 kilos in France, 27 kilos in Italy and 21 kilos in Greece. With the exception of Portugal, the share of aquaculture in the market for fish and fishery products is just as strong in the Mediterranean countries as in the other countries of the European Union. However, this high share of aquaculture is mostly contributed by crustaceans and shellfish.
7. Meeting of Ministers of Agriculture and Fisheries of CIHEAM Member Countries, 2008/02/04, Zaragoza (Spain)